Focal non-typhoidal Salmonella infections from a single center in Malaysia - Lee, W.S.; Hafeez, A.; Hassan, Hamimah; Raja, N.S.; Puthucheary, S.D. (SEAMEO Regional Tropical Medicine and Public Health Network, 2005)
A retrospective review of patients with focal non-typhoidal Salmonella (NTS) infection was performed to determine its features and outcome. All patients with focal NTS infection admitted to the University of Malaya Medical Center, Malaysia, from 1993 to 2002 were studied. More than half (58) of the 35 cases (54 male, median age 39 years, range 1.5 months to 79 years) were immunocompromized or had chronic medical conditions. One-third of the patients (34) had superficial infections (lymphadenitis or subcutaneous tissue infection) and all recovered with antimicrobial therapy alone. Deep infections (66) noted were: meningitis (9), osteomyelitis or arthritis (26), abscesses of the gastrointestinal tract or adjacent organs (20), and others (11). Deep infections were more likely to occur in the extremes of age (<6 months or >60 years, p< 0.04), associated with adverse outcomes with an overall mortality rate of 9, or required major surgery (15).